(untitled) (Baghdad Science Journal, 2025)
This study included estimation of glutathione (GSH) and Malondialdehyde (MDA) levels in the serum of diabetic patients type II who are treated with a polyherbs mixture (Nigella sativa, Trigonella foenum-graeum, Cyperus rotundus and Teucrium polium) for three months of treatments. Seventy samples of diabetic patients Type II male and females with age about (35-60) years were taken including 44 samples for group one (24 male, 20 female) who used herbs accompanied with chemical treatment (drugs) and 26 samples for the second group (13male and 13 female) who used herbs only. These groups were compared with 60 samples obtained from healthy persons (29 male, 31 female) at the same age of patients as a control group. Effect of age and treatment for two groups (first and second) of diabetic patients were studied before treatment and after three months treated with polyherbs and chemical treatment (antidiabetic drugs) for first group of patients and polyherbs mixture only for second group of patients. Also these effects were checked for two groups after stop the treatment for one month later. The results were shown that there is an increase in the level of MDA in the serum of diabetic patients then decreased of its value after treatment with polyherbs mixture for three months 1st, 2nd, 3rd, compared to control at deferent rang .When stopping of polyherbs mixture treatment for both groups of diabetic patients, there is an increase in the level of MDA than the level of it before stop treatment. At the same time, the results were showed decrease in the level of GSH in serum for both groups of diabetic patients at different range of age before treatment with polyherbs mixture compared to control group. But when treatment takes place for three months, there is an increase in the level of this parameter GSH and after one month of stop treatment, the level of glutathione was more decreased than the result before stop this treatment at the same range of ages. On the other hand, the results showed a significant increase of free radicals during the measurement of MDA level and a decrease of antioxidants such as glutathione of diabetic type II patients compared to the control group (Healthy persons). The research also included study the effect of the other factors such as duration of disease state, glucose concentration, other diseases, body mass index (obesity) and smoking on lipid per oxidation and antioxidants for diabetic patients with who treated before and after treatment at different intervals of time polyherbs mixture . It was observed that there is a significant increase in the level of MDA and blood glucose and not significant in BMI as increasing the time duration of diabetes, but there is no any effect was observed for the effect of sex, smoking in these two groups of patients.